The self-managing school - Caldwell, Brian J.; Spinks, Jim M. (London ; New York : Falmer Press, 1988)
This book is divided into three parts: A framework for self-management; The process of collaborative school management; Making it work.
Keywords: Education; School management; School management and organization; School management and organization -- Decision making; Public schools -- Business management